2022
DOI: 10.1128/spectrum.02371-21
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurrence of Rare ArmA-, RmtB-, and KPC-2–Encoding Multidrug-Resistant Plasmids and Hypervirulence iuc Operon in ST11-KL47 Klebsiella pneumoniae

Abstract: Carbapenemase-producing Klebsiella pneumoniae have become a great challenge for antimicrobial chemotherapy, while aminoglycosides can lower the mortality rate effectively in combination therapy with them. Unfortunately, we isolated two K. pneumoniae from blood sample of patients that not only exhibited high-level resistance to carbapenems and aminoglycosides but also showed the unusual co-occurrence of the rmtB , armA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…Interestingly, those strains were mostly originated in China and seemed to be associated with K. pneumoniae ST11 type. 4 , 19 , 54 , 63–69 These data implied that plasmids carrying this genetic background have been confined to K. pneumoniae ST11 so far and circulated since 2010 in mainland China. This resistant genetic background usually integrated into a fosA3 -positive IncR-IncFII plasmid which was composed of three genetically and physically distinct modules: a pHN7A8-derived module which contains fosfomycin resistance gene fosA3 and IncFII replicon, a pKPC-LK30-derived core module which harbors bla KPC-2 gene and IncR replicon, and another 10 kb module.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Interestingly, those strains were mostly originated in China and seemed to be associated with K. pneumoniae ST11 type. 4 , 19 , 54 , 63–69 These data implied that plasmids carrying this genetic background have been confined to K. pneumoniae ST11 so far and circulated since 2010 in mainland China. This resistant genetic background usually integrated into a fosA3 -positive IncR-IncFII plasmid which was composed of three genetically and physically distinct modules: a pHN7A8-derived module which contains fosfomycin resistance gene fosA3 and IncFII replicon, a pKPC-LK30-derived core module which harbors bla KPC-2 gene and IncR replicon, and another 10 kb module.…”
Section: Discussionmentioning
confidence: 92%
“… 2 , 3 Among CRE, the carbapenem-resistant Klebsiella pneumoniae (CRKP) is a taxon of considerable interest. 4 , 5 Three highly reactive carbapenemases have been described in CRKP, known as class A KPC-type, class B NDM-type, and class D OXA-48-like. 6 , 7 These carbapenemase-encoding genes are usually located on drug-resistant plasmids with the ability to transfer between bacterial cells through the concerted activities of mobile genetic elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the emergence of conjugative virulence plasmids also encoding antimicrobial resistance or MDR remains uncommon. Zhou et al described the conjugative plasmid p1864-1 of the IncFIB/IncH1B type, which harbored both resistance genes and the iuc operon ( 29 ). Many studies have suggested a close relationship between the IncF subtype IncFIB/IncFII plasmids and AMR genes ( 30 33 ), whereas a recent study showed that the IncFIB K replicon has a significant impact on promoting the development and replication of virulence plasmids, especially the plasmid-borne iuc genes normally harbored by an IncFIB K replicon ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, bacterial clones were diluted with saline to a concentration of approximately 10 8 CFU/ml, and then 1 μl bacterial clones were dropped on CAS and King's B (2:1) plates. After incubation for 24 h at 37°C, siderophore production was determined by the presence of an orange halo around the bacterial colonies (Zhou et al, 2022).…”
Section: Quantitative Siderophore Production Assaymentioning
confidence: 99%